Stabilization of influenza virus replication intermediates is dependent on the RNA-binding but not the homo-oligomerization activity of the viral nucleoprotein. - Vreede, F; Ng, A; Shaw, P; Fodor, E (2011)
The influenza virus nucleoprotein (NP) is believed to play a central role in directing a switch from RNA genome transcription to replication by the viral RNA polymerase. However, this role has recently been disputed with the proposal of alternative regulatory mechanisms. It has been suggested that the expression of viral polymerase and NP allows genome replication by stabilization of cRNA replication intermediates and complementary ribonucleoprotein (cRNP) assembly. Here, we demonstrate that the RNA-binding activity of NP is necessary for stabilization of cRNA, whereas, surprisingly, homo-oligomerization of NP is not essential. However, both RNA binding and homo-oligomerization activities are essential for genome replication.